Progressive increase of matrix metalloprotease-9 and interleukin-8 serum levels during carcinogenic process in human colorectal tract. - Fiorella Biasi; Tina Guina; Marco Maina; Mario Nano; Alessandro Falcone; Emiliano Aroasio; Giorgio Maria Saracco; Mauro Papotti; Gabriella Leonarduzzi; Giuseppe Poli (PLoS ONE, 2012)
BACKGROUND: Inflammatory reactions, known to promote tumor growth and invasion, have been found associated with colorectal carcinoma (CRC). Macrophages are the chief component of the inflammatory infiltration that occurs early in the progression from non-invasive to malignant tumor, with a switch from the pro-inflammatory phenotype to the tumor-promoting phenotype. Tumor and stroma are additional sources of inflammation-related molecules. The study aimed to evaluate, during colorectal carcinogenesis from benign to malignant phases: i) the trend of serum levels of IL-8, IL-6, TGFβ1, VEGF and MMPs; ii) the parallel trend of CRP serum levels; iii) derangement of the principal TGFβ1 receptors (TGFβ1RI/RII) in tumor tissues. METHODOLOGY/PRINCIPAL FINDINGS: 96 patients with colon adenomas or CRC at different stages of progression, and 17 controls, were recruited. Serum IL-8, IL-6, TGFβ1, VEGF, MMPs and CRP levels were analyzed before endoscopy or surgery. TGFβ1 receptors were evaluated in adenoma biopsies and surgically-removed colorectal adenocarcinomas. Serum levels of IL-8 in adenocarcinoma patients were increased from stage II, when also the enzymatic activity of MMP-9 increased. Of note, the increasing trend of the two serum markers was found significantly correlated. Trend of serum CRP was also very similar to that of IL-8 and MMP-9, but just below statistical significance. TGFβ1 levels were lower at stage III CRC, while IL-6 and VEGF levels had no significant variations. In tissue specimens, TGFβ1 receptors were already absent in about 50% of adenomas, and this percentage of missing receptors markedly increased in CRC stages III and IV. CONCLUSIONS: Combined quantification of serum IL-8, MMP-9 and CRP, appears a reliable and advanced index of inflammation-related processes during malignant phase of colorectal carcinogenesis, since these molecules remain within normal range in colorectal adenoma bearing patients, while consistently increase in the blood of CRC patients, even if from stage II only.